Improving production logistics through materials flow control and lot splitting - Gomes, Catarina (2016)
Competitive advantage of make-to-order manufacturing companies is highly dependent on their capability to offer short delivery times and on time delivery. This calls for effective production and materials flow control – a core part of production logistics. This paper applies discrete simulation to study the delivery performance of a make-to-order manufacturing system configured as a general flow shop, when operated under two card-based material flow control mechanisms: CONWIP and GKS. The influence of two lot splitting strategies on the performance of these mechanisms is also evaluated. Results show that GKS clearly outperforms CONWIP and that splitting strategies have a positive impact on the performance of both mechanisms. GKS also showed to be particularly robust to the variation of the number of production authorisation cards used. This, together with the fact that the card-based mechanisms require little data handling and simplify production control, makes GKS attractive for practical application in make-to-order companies.